Snailed It! Inside the Shell: Using Augmented Reality as a Window Into Biodiversity - Merino, Cristian; Iturbe-Sarunic, Catalina; Miller, Brant G.; Parent, Christine E.; Phillips, John G.; Pino, Sonia; Garrido, José Miguel; Arenas, Andoni; Zamora, Juan (Frontiers in Education, 2022)
Snails have occupied an important role in the ideology and religion of the ancient American peoples, who considered them to be magical and used them in ritual ceremonies as ornaments, musical instruments, and architectural elements. Today, they are a valuable study system for understanding biodiversity and evolution, due to their remarkable ecological and morphological diversity. Given that many endemic snails are of conservation concern, and that most South American species are poorly studied, there is a need to engage the public through language that is understandable and scientifically based, conveying the importance of biodiversity. However, not all biodiversity can be seen with the naked eye. Herein, we describe how we utilize snails and their shells to engage citizens and train teachers to promote the many different facets of biodiversity. Through design-based research oriented towards educational innovation, we created a teaching-learning sequence with immersive technology through the following stages of work: 1) produce a teaching-learning sequence and accompanying mobile device application (for Android on GooglePlay), 2) evaluate the impact of the educational resource, and 3) conduct research through a pre- and post-test design on the learning outcomes of participants. In this work, we first present the field experience where scientists, teachers, and pre-service teachers worked together to find snails from northern Chile to Chiloé Island. Some results from this research stage are: criteria for designing a teaching-learning sequence (e.g., how to utilize place as an opportunity for learning science with developmentally appropriate technologies identified for every phase of the sequence), modeling relevant phenomena about biodiversity and ecosystems through snails, scaffolding for teachers implementing the sequence, and activities that enhance STEM education. A teaching-learning sequence that addresses snails as study objects for 4th grade is presented and validated, allowing us to continue the next phase of our research with schools. Results from implementation, iterations and their implicances will be approached in a second article.